Management challenges in mHealth: failures of a mobile community health worker surveillance programme in rural Nepal. Issue 1 (17th January 2017) - Meyers, David J; Filkins, Malina; Harsha Bangura, Alex; Sharma, Ranju; Baruwal, Ashma; Pande, Sami; Halliday, Scott; Schwarz, Dan; Schwarz, Ryan K; Maru, Duncan S R
Abstract : Community health workers form the backbone of healthcare systems globally. The rapid expansion of mobile communications systems represents an opportunity to improve the productivity of community health workers in rural areas. Here, we describe a programme in rural Nepal that aimed to implement a mobile phone system for collecting health surveillance data, yet did not reach its fullest potential due to several programme management challenges during the implementation of the surveillance programme. Despite early successes with the mobile phone system itself, the programme ultimately failed due to leadership transitions, poor process design and a lack of consistent vision of how to operationalise the data. This field report provides important insights into the design, maintenance and pitfalls of similar community-based mobile health initiatives and technology innovation projects in general.